Free-Breathing, Non-Gated Heart-To-Brain CTA in Acute Ischemic Stroke: A Feasibility Study on Dual-Source CT - Liu, Jiabin; Wang, Chen; Li, Qing; Duan, Xianggong; Zhu, Xiaolian; Wang, Jiahong; Du, Xiangying; Lu, Jie; Li, Kuncheng (Frontiers in Neurology, 2022)
Purpose To validate the feasibility of free-breathing, non-gated, high-pitch heart-to-brain computed tomography arteriography (CTA) in acute ischemic stroke and the capability of non-gated heart-to-brain CTA in showing cardiac anatomy. Materials and Methods The study protocol was approved by the institutional medical ethics review board. Free-breathing, non-gated, high-pitch heart-to-brain CTA was performed on patients with acute ischemic stroke referred for multimodal CT using a third-generation dual-source CT. Patients scheduled for ECG-triggered heart-to-brain CTA served as controls. Quantitative and/or qualitative image quality of the four cardiac chambers, left atrial appendage, interventricular and interatrial septa, carotid arteries, and coronary arteries were evaluated and compared between the two groups. Results Free-breathing, non-gated, high-pitch heart-to-brain CTA was performed on 30 patients with acute ischemic stroke, whereas the control group included 31 cases. There is no significant difference in the image quality of CTAs between the two groups at cardiac chambers and carotid arteries. The image quality of coronary arteries also showed no significant difference between the two groups. The mean dose length products of CTA in the two groups were 129.1 ± 30.5 mGy cm and 121.6 ± 30.3 mGy cm, respectively. Cardiac abnormality can be shown in patients with acute ischemic stroke. Conclusion It is feasible to use free-breathing, non-gated, high-pitch heart-to-brain CTA with dual-source CT in acute ischemic stroke for cardiac etiology screening.